2020
DOI: 10.1093/ptj/pzaa180
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization and Exercise Intervention for Patients With Multiple Myeloma: Clinical Practice Guidelines Endorsed by the Canadian Physiotherapy Association

Abstract: Objective Individuals with multiple myeloma (MM) often have reduced functional performance due to the cancer itself or as a direct side effect of cancer treatments. Physical therapy is a part of cancer rehabilitation; however, no guidelines are available to provide information and direction for physical therapists managing patients with MM. The goal of this guideline is to provide recommendations based on a systematic review and consensus process that physical therapists can use to manage pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…However, expanding access to appropriate and effective interventions to address any concerns identified through such assessment is also needed. This may include myeloma-specific patient education, self-management support, or supportive care services to address physical and psychological issues including symptom control, physical fitness, emotional health, and social well-being (Jeevanantham et al, 2020;Shapiro et al, 2021;Snowden et al, 2017). Specialized oncology nurses and nurse practitioners may be well positioned to lead innovations in this area.…”
Section: Discussionmentioning
confidence: 99%
“…However, expanding access to appropriate and effective interventions to address any concerns identified through such assessment is also needed. This may include myeloma-specific patient education, self-management support, or supportive care services to address physical and psychological issues including symptom control, physical fitness, emotional health, and social well-being (Jeevanantham et al, 2020;Shapiro et al, 2021;Snowden et al, 2017). Specialized oncology nurses and nurse practitioners may be well positioned to lead innovations in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Although MM in most cases responds to chemotherapy and radiotherapy, bone changes may still progress, leading to pathological fractures. In order to maintain fracture stability, surgical intervention is often required, involving internal fixation or arthroplasty [16,17,18]. The aim of this study was to provide guidelines for inpatient rehabilitation in the treatment of pathological fractures resulting from the course of multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, two reported that it would be preferable to have guidelines, and three suggested general strategies and procedures. Only one article, published by the Canadian Physical Therapy Association, provided practical recommendations developed by physical therapists in conjunction with myeloma patients ( Jeevanantham et al, 2021 ). The guidelines provide 30 action statements for the safe and optimized application of physical exercise and management of the specific challenges that this patient group faces.…”
Section: Methodsmentioning
confidence: 99%